Hemosiderin quantification in hemophilic arthropathy using quantitative magnetic resonance imaging - Sedaghat, Sam; Luck, Jame V.; von Drygalski, Annette; Fu, Eddie; Park, Jin Il; Gehling, Kim Gina; Ma, Yajun; Ball, Scott; Chang, Eric Y.; Du, Jiang; Jang, Hyungseok (Scientific reports, 2025)
The goal of this study is to quantify hemosiderin deposition in the knee joint tissues of hemophilic arthropathy (HA) patients using quantitative susceptibility mapping on MRI. Knee synovial tissues from HA patients and controls without hemophilia were included. The tissues underwent ultrashort echo time quantitative susceptibility mapping (UTE-QSM) and clinical MRI. HA tissues were processed histologically with Perl’s Prussian Blue (PPB) staining to identify iron contents. Seven regions of interest were drawn in each tissue, and the susceptibility values were tested. Moreover, the association between the estimated magnetic susceptibility and the iron contents quantified by histology was investigated. Nine synovial tissues were procured from total knee arthroplasty of hemophilia patients (males, 40.8 ± 9.0 years), and three synovial tissues were harvested from cadaveric knee joints of donors without hemophilia as controls (males, 72.0 ± 12.8 years). The estimated susceptibility values (ESVs) showed significant differences between HA and control samples. Accordingly, HA tissues presented a mean ESV of 0.48 ± 1.08 ppm and control tissues of -0.13 ± 0.12 ppm (p < 0.05). A significant linear correlation was found between the iron level quantified by histology (PPB stain) and the ESV estimated by UTE-QSM (R = 0.908, p < 0.01). There was a significant difference in the susceptibility in high load (HL) tissues compared to low load (LL) tissues (ESV = 5.57 ± 1.23 ppm for HL vs. 0.57 ± 0.85 ppm for LL, p < 0.001). Reliable hemosiderin quantification in joint tissues of HA patients can be achieved using MRI based on quantitative susceptibility mapping.